Pertanggungjawaban Pidana Terhadap Kerusakan Lingkungan Akibat Pengolahan Material Oleh PT Tukad Mas Kota Bima - Hajairin Hajairin; Gufran Sanusi; Aman Ma’arij (SASI, 2021)
Material processing by PT Tukad Mas Kota Bima which has a negative impact, namely the existence of pollution or environmental damage in the East Rasa Nae Subdistrict, Bima City, so that it can be held accountable under criminal law, civil law and administrative law. The purpose of this study was to determine the form of criminal liability for environmental damage due to material processing by PT Tukad Mas Kota Bima. The research method used is empirical legal research with data collection techniques through interviews and documentation. The findings of this study indicate that legal liability for environmental damage due to material processing by PT Tukad Mas Kota Bima can be seen in aspects of criminal law, civil law and administrative aspects. However, the Bima City Government through the Environmental Service has only given a written warning to PT Tukad Mas Kota Bima, which has been operating for decades. Whereas empirical facts have shown that there is quite severe damage, such as waste disposal that can have a health impact on the community and natural damage due to excavations carried out. Criminal liability should be a special concern, NGOs and the community even report on environmental crimes, the report is because the result of material processing causes environmental pollution as one of the elements of criminal acts against environmental pollution.